Undercover : reporting for the New York World 1887-1894 - Bly, Nelly (Minnesota Archive, 2014)
A compilation of original, unabridged newspaper articles by Elizabeth Jane Cochran, who wrote under the name Nellie Bly. By disguising her voice, mannerisms and appearance, this intrepid reporter gained admittance to New York's vast cultural underground of criminals, con artists, and frauds, and fearlessly exposed their scams and shenanigans to a rapt and growing audience on the front pages of Joseph Pulitzer's The New York World. Bly's reporting introduced the era of muckraking journalism, and originated the practice of undercover reporting that has remained a vital journalistic art to the present day.
Keywords: Periodismo -- EEUU -- Historia -- Siglo 19